Pengaruh Overcommitment Pada Keterikatan Kerja Dengan Konflik Kerja-Keluarga Sebagai Pemediasi - SARI, KURNIA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The purpose of this research is to examine the influence of overcommitment to job engagement and the mediating role of work-family conflict in effect between overcommitment and job engagement. This study uses 206 nurses as respondents, the sample consists of 169 women and 37 men. Simple regression and Sobel Test were used as a statistical method to test the proposed hypotheses. The result shows that overcommitment has a positive influence and significantly relating to job engagement. It is also found that overcommitment has a positive influence and significantly relating to work-family conflict. Meanwhile work-family conflict has negative influence on job engagement, but not significant. Thereby, work-family conflict has no impact as a mediator in effect between overcommitment and job engagement.